السمات الهندسية في منظومة زخارف شبابيك مسجد أحمد بن طولون - الصبان، محمد حسين علي محمود (الجمعية العربية للحضارة والفنون الإسلامية, 2021)
النوافذ من العناصر المعمارية الهامة ومن أقدمها وقد استخدمها الانسان للإنارة والتهوية واهتم بتطويرها فالمصري القديم عمل على ربط الفراغ المعماري الداخلي والمحيط الخارجي بعمل فتحات كنوافذ علوية جانبية ثم تطورت علي مر العصور الي ان جاء الفنان الإسلامي فأضاف الشخصية الإسلامية على العمارة وطور عنصر النوافذ بداية من عصر الامويين، واكسب هذا الفراغ طابعا مميزا في العمارة الاسلامية. وقد أتجه الفنان في الحضارة الاسلامية الي استخدام اساليب واشكال فنية ذات طابع خاص لزخرفة النوافذ تتوائم والمفاهيم التي فرضتها الحضارة الاسلامية، فأصبحت سمة من سماتها وتعتبر الاشكال الهندسية التي تناولها الفنان في ذلك العصر أحد انواع التجريد الذي برع في استخدامها بعد تفهم القوانين الرياضية والاسس الهندسية التي تقوم عليها تلك الاشكال. وعمارة المسجد الطولوني (876-879 ميلادية) تمتاز بوجود نوافذ في جدران المسجد الأربعة يبلغ عددها 128 نافذة، استطاع الفنان المصمم ان يبدع في زخرفة شبابيك تلك النوافذ ويخلق اشكال زخرفية غاية في التنوع اخضعها لحدود الهندسة وعلم الرياضيات، لذا نجد اشكال فريدة لم يكن لها نظائر من قبل وتشمل خصائص الزخرفة الاسلامية مثل التكرار والتماثل وتلك سمة اساسية في جميع الزخارف الطولونية وهو تكرار لا يمل المرء متابعته وقد يختفي العنصر الزخرفي بين عناصر اخري شبيه ولكنه لا يتلاشى وتتحرك الوحدات الزخرفية وهي ثابتة وتتجدد وتمتد الي ما لانهاية. وتتلخص مشكلة البحث في ان منظومة زخارف شبابيك مسجد بن طولون رغم اهميتها وتفردها لم تحظ بدراسة سابقة تسهم في تنمية الرؤية التصميمية وتعزيز المحتوي المعرفي وما يحتويه من ابعاد التصميم الزخرفي الإسلامي. ويهدف البحث الكشف عن السمات الهندسية في منظومة زخارف شبابيك مسجد أحمد بن طولون والتعرف على أبعادها الفنية في مجال التصميمات الزخرفية.
Windows are one of the important architectural elements and among the oldest, and man used them for lighting and ventilation and took care of developing them. The ancient Egyptian worked to connect the internal architectural space and the outer perimeter by making openings as upper side windows and then developed over the ages until the Islamic artist came, adding the Islamic character to architecture and developing the windows element beginning in the Umayyad era. And this vacuum gained a distinctive character in Islamic architecture In the Islamic civilization, the artist tended to use artistic methods and forms of a special character for window decoration that are compatible with the concepts imposed by the Islamic civilization, so it became a feature of its features and the geometric shapes that the artist dealt with in that era is considered one of the types of abstraction that he excelled in using after understanding the mathematical laws and engineering foundations that Underpin those shapes Passers-by of the Tulun Mosque (876-879 AD) are distinguished by the presence of windows in the four walls of the mosque, numbering 128 windows. The designer was able to innovate in the decoration of the windows of these windows and create very diverse decorative shapes that subjected them to the limits of geometry and mathematics, so we find unique shapes that were not Analogs from before and includes the characteristics of Islamic decoration such as repetition and symmetry, which is an essential feature in all Tulunid motifs and it is a repetition that one does not wish to follow, and the decorative element may disappear between similar elements, but it does not vanish, and the decorative units move and are fixed, renewed and extended to infinity. The research problem is summarized in the fact that the system of decoration of the windows of the Ibn Tulun Mosque, despite its importance and uniqueness, has not received previous studies that contribute to the development of the design vision and the enhancement of the cognitive content and the dimensions of the Islamic decorative design.
Keywords: الفن الإسلامي -- العناصر المعمارية -- التصميمات الزخرفية -- عمارة الشبابيك -- ابن طولون، محمد بن علي بن أحمد، ت. 953 هـ